Development and Growth of Financial Sector Stock Market on Investment Climate: Study on Bank Syariah Indonesia and Bank Mandiri - Ary Dean Amri; Dea Anjelinah; Fidyah Safitri; Duwi Puspita; Neni Yuana; Andini Destri Aulia; Asraf Mustafa (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
The purpose of this study is to analyze the development and growth of the stock market in the financial sector and the comparison between Bank Syariah Indonesia Tbk (BRIS) and Bank Mandiri Persero Tbk (BMRI) on the investment climate in Indonesia. This research method uses quantitative data, as the name implies, many are required to use value figures from data collection, interpretation of the data, and the appearance of the results. This study uses variables consisting of Dependent Variables, namely Investment Climate, and Independent Variables, namely the Development and Growth of the Stock Market in the Financial Sector and Comparison between Bank Syariah Indonesia Tbk (BRIS) and Bank Mandiri Persero Tbk (BMRI). The source of the data was obtained data from the Central Statistics Agency (BPS), Bank Syariah Indonesia Tbk (BRIS), and Bank Mandiri Persero Tbk (BMRI). The results of the study concluded that if the growth and development of the Stock Market in the financial sector increased by 0.01 (1%), then the Investment Climate would increase by 0.390736. Then if there is an increase in the comparison rate between Bank Syariah Indonesia Tbk (BRIS) and Bank Mandiri Persero (BMRI) 0.01 (1%), the Investment Climate will decrease to 1.370777. Based on statistical test F of 8.19119, and probability value (Prob) of 0.0011590 < 0.05. This states that the Growth and Development of the Stock Market in the financial sector and the comparison between Bank Syariah Indonesia Tbk (BRIS) and Bank Mandiri Persero (BMRI) together have a positive impact on the investment climate with a certainty level of 0.671892 (67.2%). The variation in changes in the rise and fall of the investment climate can be influenced by the growth and development of the stock market in the financial sector and the comparison between Bank Syariah Indonesia Tbk (BRIS) and Bank Mandiri Persero (BMRI) of 67.2%, then 32.8%, the rest is explained by other factors. R2 adjusted the 589865 figures, showing that the probability level of the investment climate of the model used is 59%.